Raza Ali Abidi’s Scholarly and Literary Services - Ahmed Awan, Muhammad; Shar, Shezra (sourcecoder, 2022)
Raza Ali Abidi was born 30 November 1935 in Rookree, Uttarkhand (India). He moved to Karachi along his family in 1950, and then migrated to London & worked for the BBC (URDU) 1972 till 2008. He got education from a renowned institute which is Islamia College. He is Urdu travelogue, Fiction writer, Journalist, Broadcaster, Sketcher and well known children’s story writer. Raza Ali Abidi has gained fame for being an author, explorer, writer and Journalist, Some acclaimed books of the Raza Ali Abidi are Urdu ka haal, Jurnale Sarak, Jahaze Bhai, Sher Darya, Keetabein Apney Aaba Ke, Jaan Sahib, Tees Saal Bad, Apne Awaz etc.